Purely Maximal Sub-modules - Hamdi, Halah Qahtan; Al-Mothafar , Nuhad Salim (Iraqi Journal of Science, 2026)
In this paper, we present the notion of a purely maximal sub-module,  also we consider some properties of this concept, and we Tresearch some relationships between purely maximal sub-modules and some other related ideas. Furthermore, we give purely-radical modules and purely local modules.